Guarantees for Parliamentary Elections - Zangana, Ismail Najmaldin; Saeed, Zana Jalal (Journal of Legal and Political Studies, 2017)
Parliamentary election, democratic process for the award of future and temporary power, in terms of which the people exercise their sovereignty, and expressed their opinion explicit on people who claim access to the chairs of governance and power, on such case the study of such the operation of the party statement of the general concept and its outskirts, find and be endorsed in the embodiment of guarantees freedom of expression in a healthy and fair is very important , it comes in application of the constitutional principle that came shift for the each constitutional texts in countries that claim democracy in its judgment system. We have tried hard to address this important develops by analyzing the concept and guarantees relating to parliamentary election in the context of two main axes independent preface, in the first preface we examined the concepts related to parliamentary elections and their importance and its role in society, and we have dedicated the second preface to analyze the constitutional guarantees of the elected process which is in turn subdivided in to a public guarantees and private, any pictures of them and their impact on the provision of vocabulary appropriate to hold a free and fair election in the community, and we finished the study by the most prominent of what we have achieved results and we made a number of recommendation thereon.
Keywords: election; democratic; constitutional principle; sovereignty